Effect of corticosteroid use by dose on the risk of developing organ damage over time in systemic lupus erythematosus—the Hopkins Lupus Cohort. Issue 1 (11th March 2015) - Al Sawah, Sarah; Zhang, Xiang; Zhu, Baojin; Magder, Laurence S; Foster, Shonda A; Iikuni, Noriko; Petri, Michelle
Abstract : Objectives: The impact of corticosteroids on the risk of organ damage in the context of clinical end points endorsed in some systemic lupus erythematosus (SLE) clinical trials is underexplored. Methods: We analysed data from the Hopkins Lupus Cohort using Cox proportional hazards models to understand the impact of exposure to different corticosteroid doses on the risk of developing any new organ damage or any new organ damage at the individual organ systems over time. Results: Mean prior prednisone dose, recent disease activity and immunosuppressant use during follow-up, as well as organ damage score at cohort entry, were significant independent predictors of the risk of developing any new organ damage. Even after adjustment for recent disease activity, there was a dose-response relationship across the different levels of exposure to prednisone during follow-up and the risk of developing any new organ damage. The risk more than doubled in patients exposed to a mean prior prednisone dose of ≥20 mg/day versus <7.5 mg/day (HR=2.514, p<0.001). It was estimated that a 1 mg/day increase in prior prednisone dose during follow-up was associated with a 2.8% increase in the risk of developing new organ damage. For individual organ systems, exposure to a mean prior prednisone dose of ≥7.5 mg/day versus <7.5 mg/day significantly increased the risk of developing cataracts (HR=2.41, p<0.001), osteoporotic fractures (HR=2.16, p<0.001) and cardiovascular damage (HR=1.54, p=0.041), but showed no significant difference for renal damage (HR=1.44, p=0.163) or for other individual organ systems. Conclusions: Organ damage in SLE is multifactorial; corticosteroid treatment and disease activity play a role.